2023
DOI: 10.1111/jsr.14072
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study on the effect of rhythmic masticatory muscle activity (RMMA) clusters on sleep fragmentation and severity of orofacial muscle pain in sleep bruxism

Helena Martynowicz,
Gilles Lavigne,
Takafumi Kato
et al.

Abstract: SummaryRhythmic masticatory muscle activity (RMMA) is a periodic muscle activity that characterises sleep bruxism (SB) events. These can occur as a single event, in pairs, or in clusters. Since RMMA episodes often occur in clusters and the relevance of this occurrence is unknown, we conducted a study to investigate the effect of RMMA clusters on sleep fragmentation and the severity of orofacial muscle pain. This study involved a secondary analysis using data from 184 adult subjects with orofacial muscle pain w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…It can occur as a single event, in pairs or in clusters, and is connected with the severity of orofacial pain. 33 During the implementation of the present project, the research results facilitated the decision on the indicated psychological or psychiatric consultation for patients treated for TMD. Moreover, the patients expressed their satisfaction with the recommendation of a necessary consultation regarding their psycho-emotional state.…”
Section: Discussionmentioning
confidence: 98%
“…It can occur as a single event, in pairs or in clusters, and is connected with the severity of orofacial pain. 33 During the implementation of the present project, the research results facilitated the decision on the indicated psychological or psychiatric consultation for patients treated for TMD. Moreover, the patients expressed their satisfaction with the recommendation of a necessary consultation regarding their psycho-emotional state.…”
Section: Discussionmentioning
confidence: 98%